Ha Tinh Farmer Union 5-year Action Plan (No.11-CTHD/HNDT 2018-2023) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Climate services will be integrated in the planning and implementation of all activities, estimated to benefit 200000 households. Ha Tinh Farmer's Union is running the Participatory Scenario Planning (PSP).